Fear and learning in medieval Islam. (1st September 2020) - Vignone, Joseph Leonardo
Abstract : In this article I argue that a specific experience of fear was adopted by the Islamic scholarly class (ulema) from the mid-tenth century onwards as an affective descriptor of their profession. This fear - khashya, which I translate here as 'dread' - appears in the Qur'an as an apprehensive emotion that those who possess knowledge feel towards God. In modern scholarship, it has often been cited as a term used by scriptural and mystical commentators to explain proper piety, usually figured as one of several kinds of fear falling under the broader term khawf. In his commentary on Abu Isma'il al-Ansari's celebrated text of mystical terminology, Manazil al-sa'irin, Ibn Qayyim al-Jawziyya distinguishes khashya from khawf, citing the Qur'an in order to cast the latter as a baser experience of fear characteristic of common believers. Ibn al-Qayyim argues that it is exclusively the ulema who experience khashya, for only they enjoy intimate knowledge of God imparted by their erudition. While otherwise absent from the Manazil's commentary tradition, this argument appears prominently across works of scholarly ethics (adab) authored by ulema living from the mid-tenth century through Ibn al-Qayyim's lifetime, almost always in reference to the intellectual pursuits that they believed afforded them a unique relationship with God. Attended by a semantic shift in Arabic lexicography favoring this interpretation of khawf and khashya, by the tenth century the affectively resonant language of dread became a pervasive way the ulema justified the social and cosmological hierarchy of Muslims over which they claimed to preside.